An examination of the effects of Internet banking, CRM, and product excellence on customer loyalty at State-owned Islamic Bank located in Central Java - Romadhon, Hindun Mutiara; Widowati, Mustika; Hasanah, Siti (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
This study aims to analyze the significance of product excellence, internet banking, and customer relationship management on customer loyalty at the State-owned Islamic Bank located in Central Java. The population in this study were the customers with the sample used in this study 118 customers were selected using the Simple Random Sampling technique. This research used the Multiple Linear Regression analysis, as well as both partial and simultaneous tests, the Coefficient of Determination test. The results finds that the hypotheses and discussion show that product excellence, internet banking, and customer relationship management have a positive and significant effect on loyalty at the State-owned Islamic Bank located in Central Java both partially and simultaneously.